PENEGAKAN HUKUM TERHADAP PENCURIAN IKAN (ILLEGAL FISHING) DI WILAYAH PERBATASAN PROVINSI KEPULAUAN RIAU - Wasrizal, Wasrizal (Universitas Internasional Batam, 2020)
As a border region, Riau Islands Province is very vulnerable to cases of illegal fishing. Such cases can occur in the territorial sea as well as in exclusion economic zones or in the open sea boundary region. The number of cases of illegal fishing in the border region raised the theme of illegal fishing for this research which refers to Law Number 45 of 2009. The purpose of this study is to record which agencies have authority in the case of cases of illegal fishing in the border region of Riau Islands Province, to analyze the actions taken by the authorities in law enforcement against those who commit illegal fishing in the border areas of Riau Islands Province, and to analyze barriers and solutions faced by the authorities in law enforcement related to illegal fishing in the Riau Islands border region by using sociological legal research methods The result of this study is the agencies that manage cases of illegal fishing are including the Directorate of Water Police of Riau Islands Regional Police, Riau Islands Province Marine and Fisheries Service, Fisheries Court at Tanjungpinang State Courts and Indonesian  Riau Islands Navy Force. Each of them has their respective authority in accordance with the provisions of the applicable legislation which in carrying out these authorities they face obstacles and try to provide solutions in solving cases of illegal fishing in the border region of Riau Islands Province.